Studies of Power Conversion Efficiency and Optical Properties of Ni3Pb2S2 Thin Films - Ho, Soon Min (UI Scholars Hub, 2017)
Ni3Pb2S2 thin films were prepared by using a chemical bath deposition method. In this work, solar cells were fabricated using these materials as absorber layers. Power conversion efficiency testing will be carried out. The results show that these absorbent materials exhibit an open circuit voltage of 0.61 V, a short circuit current density of 9.9 mA/cm2, a fill factor of 0.47 and a power conversion efficiency of 2.7%.